Potent and selective inhibition of SH3 domains with dirhodium metalloinhibitors1. Issue 8 (14th August 2015) - Vohidov, Farrukh; Knudsen, Sarah E.; Leonard, Paul G.; Ohata, Jun; Wheadon, Michael J.; Popp, Brian V.; Ladbury, John E.; Ball, Zachary T.
<x xml:space="preserve">Abstract</x> Specific, designed histidine–rhodium interactions allow a metallopeptide to bind Lyn kinase with nanomolar affinity and to activate kinase activity.